2019
DOI: 10.3390/medicina55080459
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Microbiota: What Do We Know about It at Present?

Abstract: The human microbiota is a variety of different microorganisms. The composition of microbiota varies from host to host, and it changes during the lifetime. It is known that microbiome may be changed because of a diet, bacteriophages and different processes for example, such as inflammation. Like all other areas of medicine, there is a continuous growth in the area of microbiology. Different microbes can reside in all sites of a human body, even in locations that were previously considered as sterile; for exampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 95 publications
0
16
0
3
Order By: Relevance
“…In this context, aside from the role of pathogenic bacteria, the role of the microbiota was studied in the context of IBS. Considering the active implication of the gut microbiota for body homeostasis and human behavior [74,75], the "second brain" from the gut was found to be the missing link in the communication between the brain and the gut. Balmus et al [76], Mari et al [77] and Actis et al [78] offered a thorough description of the implication of the gut microbiota in IBS and in bowel inflammatory disorders.…”
Section: Irritable Bowel Syndrome Pathophysiology and Promoting Factorsmentioning
confidence: 99%
“…In this context, aside from the role of pathogenic bacteria, the role of the microbiota was studied in the context of IBS. Considering the active implication of the gut microbiota for body homeostasis and human behavior [74,75], the "second brain" from the gut was found to be the missing link in the communication between the brain and the gut. Balmus et al [76], Mari et al [77] and Actis et al [78] offered a thorough description of the implication of the gut microbiota in IBS and in bowel inflammatory disorders.…”
Section: Irritable Bowel Syndrome Pathophysiology and Promoting Factorsmentioning
confidence: 99%
“…Gut physiology (8,9) Nutrient production and absorption (10) Host development and physiology (11) Energy balancing (12) Metabolic functions (13,14) Immune system functions (15)(16)(17) Inflammatory processes (18) Neurons-brain-behavior system (19)(20)(21)(22) The majority of those studies cited here have demonstrated improvement in the clinical status of patients after targeted intervention influencing the gut microbiota. Similar studies relatively recently have led to definition of the so-called microbiome-gut-brain axis.…”
Section: Kubelkova Macela: Microbiota-gut-brain Axis 42 Box 2: Biolomentioning
confidence: 97%
“…Under such conditions, the increase in LPS plasma levels, caused by an imbalance in the homeostasis of the microbiota, induces a low intensity systemic inflammation which has shown to be associated with obesity, diabetes, and insulin resistance [73]. Although there is a variety of functional competencies among different intestinal microbial communities, the normal gut microbiota, which is considered the largest organ and the most complex system of microorganisms [74], plays a crucial role in most of the human health aspects and well-being, including digestion of foods, metabolic breakdown of drugs and toxins [75], nutrient metabolism [76,77], antimicrobial protection [26], development and homeostasis of immunity [75,78], the gut-brain axis [79,80], the gut-liver axis [74,81], and gastrointestinal and cardiovascular health [26,82,83]. Today, high-throughput microbiome sequencing technologyies including 16S rRna gene sequencing, whole genome metagenomics, metatranscriptomics, metaproteomics, and metabolomics, offer the most considerable insight into the gut microbiota ecosystem and their metabolic functions [68].…”
Section: Gut Microbiota Composition and Functional Aspectsmentioning
confidence: 99%
“…An imbalance or alteration in microbial composition and activity, also called "gut microbiota dysbiosis", has been associated with several clinical manifestations, although it is not yet clear if dysbiotic patterns are the cause or the consequence of the disease [84]. These disorders include obesity, type-2 diabetes mellitus, neurological and neuropsychiatric cormobidities (Alzheimer's and Parkinson's diseases, hepatic encephalopathy, autism spectrum disorder, depression, amyotrophic lateral sclerosis), allergy, carcinogenesis, autoimmune diseases (celiac disease, systemic lupus erythematosus, rheumatoid arthritis, psoriasis, atopic dermatitis), infectious diseases (Clostridium difficile infection), cardiovascular disease, and chronic kidney, hepatic, and gastrointestinal diseases [63,66,74,75,81,[85][86][87][88]. Among the most common disorders of the gastrointestinal tract related to gut microbiota dysbiosis are the two major types of inflammatory bowel disease, ulcerative colitis and Crohn's disease [75].…”
Section: Gut Microbiota Composition and Functional Aspectsmentioning
confidence: 99%